Optical and luminescence properties of noble metal nanoparticles - Weerawardene, K. L. Dimuthu M. (Kansas State University, 2017)
The remarkable optical and luminescence properties of noble metal nanoparticles (with diameters < 2 nm) attract researchers due to potential applications in biomedicine, photocatalysis, and optoelectronics. Extensive experimental investigations on luminescence properties of thiolate-protected gold and silver nanoclusters during the past decade have failed to unravel their exact photoluminescence mechanism. Herein, density functional and time-dependent density functional theory (DFT and TDDFT) calculations are performed to elucidate electronic-level details of several such systems upon photoexcitation. Multiple excited states are found to be involved in photoemission from Au₂₅(SR)₁₈– nanoclusters, and their energies agree well with experimental emission energies. The Au₁₃ core-based excitations arising due to electrons excited from superatom P orbitals into the lowest two superatom D orbitals are responsible for all of these states. The large Stokes shift is attributed to significant geometrical and electronic structure changes in the excited state. The origin of photoluminescence of Ag₂₅(SR)₁₈– nanoclusters is analogous to their gold counterparts and heteroatom doping of each cluster with silver and gold correspondingly does not affect their luminescence mechanism. Other systems have been examined in this work to determine how widespread these observations are. We observe a very small Stokes shift for Au₃₈(SH)₂₄ that correlates with a relatively rigid structure with small bond length changes in its Au₂₃ core and a large Stokes shift for Au₂₂(SH)₁₈ with a large degree of structural flexibility in its Au₇ core. This suggests a relationship between the Stokes shift of gold−thiolate nanoparticles and their structural flexibility upon photoexcitation. The effect of ligands on the geometric structure and optical properties of the Au₂₀(SR)₁₆ nanocluster is explored. Comparison of the relative stability and optical absorption spectra suggests that this system prefers the [Au₇(Au₈SR₈)(Au₃SR₄)(AuSR₂)₂] structure regardless of whether aliphatic or aromatic ligands are employed. The real-time (RT) TDDFT method is rapidly gaining prominence as an alternative approach to capture optical properties of molecular systems. A systematic benchmark study is performed to demonstrate the consistency of linear-response (LR) and RT-TDDFT methods for calculating the optical absorption spectra of a variety of bare gold and silver nanoparticles with different sizes and shapes.
Keywords: Gold and Silver nanoparticles; Luminescence; Time-dependent density functional theory; Optical properties